Solution Structure of SpoIVB Reveals Mechanism of PDZ Domain-Regulated Protease Activity - Xie, Xie; Guo, Nannan; Xue, Guangpu; Xie, Daoqing; Yuan, Cai; Harrison, Joshua; Li, Jinyu; Jiang, Longguang; Huang, Mingdong (Frontiers in Microbiology, 2019)
Intramembrane proteases hydrolyze peptide bonds within the cell membrane as the decision-making step of various signaling pathways. Sporulation factor IV B protease (SpoIVB) and C-terminal processing proteases B (CtpB) play central roles in cellular differentiation via regulated intramembrane proteolysis (RIP) process which activates pro-σK processing at the σK checkpoint during spore formation. SpoIVB joins CtpB in belonging to the widespread family of PDZ-proteases, but much remains unclear about the molecular mechanisms and structure of SpoIVB. In this study, we expressed inactive SpoIVB (SpoIVBS378A) fused with maltose binding protein (MBP)-tag and obtained the solution structure of SpoIVBS378A from its small angle X-ray scattering data (SAXS). The fusion protein is more soluble, stable and yields higher expression compared to SpoIVB without the tag. MBP-tag as a positive probe not only facilitates modeling of the structure in the SAXS envelope but also evaluate reliability of the model. The solution structure of SpoIVBS378A fits closely with the experimental scattering data (χ2=1.76). Comparing the conformations of PDZ-proteases indicate that SpoIVB adopt a PDZ-protease pattern similar to the high temperature requirement A proteases (HtrAs) rather than CtpB. We not only propose that SpoIVB uses a more direct and simple way to cleave the substrates than that of CtpB, but also that they work together as signal amplifiers to activate downstream proteins in the RIP pathway.